The Use of Crossword Labs Game to Enhance Students’ Vocabulary Mastery - Caesarani, Aprilla; Samtidar, Samtidar; Sofyan, Ryan Rayhana (Journal of Excellence in English Language Education, 2024)
The objective of this research is to find out whether the use of Crossword Labs can enhance the vocabulary mastery. This research was conducted at SMA Negeri 9 Makassar. Population in this research were students of class X SMA Negeri 9 Makassar. The researcher used purposive sampling technique for class X as the sample in this research. This research used quasi-experimental with two classes including experimental class which consist 32 students and control class which consist 32 students. The instruments used in the research was a vocabulary test divided into two, namely pre-test and post-test. The results of the mean score of experimental class was totally 75.44 which was higher than the mean score of control class which was 66.06. This shows that experimental class students more enhanced than the control class in terms of learning through using of Crossword Labs. The hypothesis test was showed with the Sig. score 0.05 > Sig. (2-tailed) score of 0.000. The researcher can be concluded that the enhancement of students' vocabulary mastery through the use of Crossword Labs game in class X.1 is successful.